Gallbladder empyema with perforation: A case report (International Seven Journal of Health Research, 2024)
Introduction: Acute cholecystitis (AC) is an inflammation of the gallbladder often caused by obstruction of the cystic duct by gallstones, responsible for 90-95% of cases. Complications include gangrene, gallbladder perforation, and empyema, which occurs in 6.3-26.6% of complicated cases and can progress to sepsis if not treated promptly. Empyema of the gallbladder is more common in men and the elderly, especially with comorbidities. Symptoms include right upper quadrant pain, fever, and nausea. Diagnosis involves ultrasound, computed tomography, and laboratory tests. Immediate treatment with antibiotics and removal or drainage of the gallbladder. Laparoscopic surgery is preferred. Objective: To demonstrate the importance of diagnosis and appropriate treatment of empyema Methods: From a medical case that occurred at the Santa Casa da Misericórdia de Presidente Prudente, and its medical records, information was collected to carry out this report. Results: Gallbladder empyema presents symptoms such as acute pain in the right upper quadrant, fever, nausea, radiation of pain to the back and shoulder, and positive Murphy's sign. With the worsening, high fever, chills and signs of sepsis appear. In the case reported here, the patient was afebrile, making it difficult to diagnose empyema. A laparoscopic cholecystectomy, the standard of care for gallstones, was performed. Conclusion: Prompt treatment with parenteral antibiotics and urgent gallbladder removal or drainage is essential to prevent serious complications and death. Laparoscopic cholecystectomy is the standard of care, offering advantages such as reduction and lower medical cost.